Analyzing IACM Implementation in Indonesia's Government Internal Audit Using Mckinsey 7S Framework - Pratama, Muhammad Agi; Umanto, Umanto (Eduvest - Journal of Universal Studies, 2025)
The capability assessment of Indonesia’s Government Internal Supervisory Apparatus (APIP) has primarily relied on the Internal Audit Capability Model (IACM) as a formal framework. However, major corruption cases persisting in institutions with high IACM levels indicate a gap between formal capability scores and the actual effectiveness of APIP in preventing corruption. This study employs a qualitative case study approach and applies the McKinsey 7S Framework to analyze organizational factors that may not be optimally captured in the current IACM assessment. The study was conducted at three government levels (central, provincial, and local) through in-depth interviews and supporting document analysis. Findings reveal that elements such as leadership style, shared values, structure, and human resource quality significantly affect APIP effectiveness, yet are underrepresented in the IACM model. This research recommends integrating the McKinsey 7S Framework into the IACM assessment process to provide a more holistic and contextually accurate representation of APIP capabilities.